Controles alternativo e biológico do ácaro-da-necrose do coqueiro Aceria guerreronis (Acari: Eriophyidae) - Silva, Maria de Jesus de Sousa (2014)
The coconut mite Aceria guerreronis Keifer, 1865 (Acari: Eriophyidae) is one of the most important pests of coconut in Brazil, especially in the Northeast. Crude cottonseed oil hasbeen recommended as an alternative to control thecoconut mite, however studies are needed for a comparative toxicity and repellency to predatory mites of the family Phytoseiidae, their main natural enemies. The phytoseiid predatory miteTyphlodromus (Anthoseius) ornatus Denmark & Muma (Acari: Phytoseiidae) is found on coconut fruits from northeasternBrazil and is possibly associated with the biological control of coconut mite. The aim of this study was to evaluate the toxicity and repellency of crude cotton seed oil to both thecoconut mite and the predatory miteas well as todeterminethe potential of this predator as a biological control agent of the pest mite. Concentration-mortality bioassays and repellency tests were used to evaluate the toxicity and repellency of crude cottonseed oil to both mites.Toxicity and repellency were comparatively evaluated withthe acaricides abamectin, azadirachtin, spirodiclofen and fenpyroximate, which are registered in Brazil to control the coconut mite. Lethal concentrations (LC) indicated that the predatory mite is about 8 times more tolerant to crude cottonseed oil than the coconut mite. Repellency tests showedthat azadirachtin acaricides, spirodiclofen, fenpyroximate and the crude cottonseed oil were repellents to coconut mite and to the predatory mite. However crude cottonseed oil wasless repellent to the predator mite. Additionally, the predatory mite showed the type II functional response showing that it is an important biological control agent of the coconut mite. The crude cotton seed oil is an alternative for the control of the coconut mite as it is toxic to this pest besides being compatible with the predatory mite, an important natural enemy of the pest mite